Blanded Learning: Solusi Model Pembelajaran Pasca Pandemi Covid-19 - Afroh Nailil Hikmah; Ibnu Chudzaifah (Al-Fikr: Jurnal Pendidikan Islam, 2020)
Online learning has become a demand for education since the Covid-19 pandemic and continues in New Normal until it continues until post-pandemic even if teachers or lecturers have to develop learning strategies. Therefore teachers/lecturers are required to be literate in technology and always up to date on learning models, one of which is Blended Learning. This research itself is expected to explain what is meant by the Blended Learning Model. And, how is the application of the Blended Learning Model when applied to the new order after the Covid-19 pandemic? The research method in this article uses a literature review, where an action on the quality and new findings of scientific work. The development of a blended learning model is a combination of learning models carried out in an online and offline context. The allocation used is 50:50, meaning that from the time allocation provided, 50% for face-to-face learning activities and 50% for online learning. The same is the case with using a 75:25 composition and doing 25:75. Blended learning model development techniques that need to be developed; 1) Face-to-face Learning Model; 2) Learning Using Electronic Teaching Materials, and 3) Learning Using Technology Media.